2019
DOI: 10.1002/nag.2943
|View full text |Cite
|
Sign up to set email alerts
|

Necessary and sufficient conditions for reaching and maintaining critical state

Abstract: Summary According to classical critical state theory (CST) of granular mechanics, two analytical conditions on the ratio of stress invariants and the void ratio are postulated to be necessary and sufficient for reaching and maintaining critical state (CS). The present work investigates the sufficiency of these two conditions based on the results of a virtual three‐dimensional discrete element method experiment, which imposes continuous rotation of the principal axes of stress with fixed stress principal values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
(66 reference statements)
3
19
0
3
Order By: Relevance
“…k n /D s is given as 300 MPa, where D s = 2R 1 R 2 /(R 1 + R 2 ) and R 1 , R 2 are the radii of particles in a given contact and k t /k n is 0.5. If the pressure of 100 kPa is considered, the average ratio of contact overlap and particle size < u n > /d 50 is around 0.16%, which is close to the value (10 −3 ) in literature [18,41]. For sample preparation, two schemes can be used to obtain an isotropic compression of the specimen: the boundary moving scheme and the internal compacting scheme [45].…”
Section: Dem Simulationsupporting
confidence: 72%
See 3 more Smart Citations
“…k n /D s is given as 300 MPa, where D s = 2R 1 R 2 /(R 1 + R 2 ) and R 1 , R 2 are the radii of particles in a given contact and k t /k n is 0.5. If the pressure of 100 kPa is considered, the average ratio of contact overlap and particle size < u n > /d 50 is around 0.16%, which is close to the value (10 −3 ) in literature [18,41]. For sample preparation, two schemes can be used to obtain an isotropic compression of the specimen: the boundary moving scheme and the internal compacting scheme [45].…”
Section: Dem Simulationsupporting
confidence: 72%
“…As recalled in the introduction, the critical state (CS) refers to a state where stresses, void ratios and fabrics tend to be steady at relatively large deformation when shear strain further increases [41]. Biaxial tests used as references have been simulated to define the critical state line which refers to a collection of critical states obtained at different confining pressures.…”
Section: Mechanical Response Along Biaxial Loading Pathsmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the relevance of the present work, it is worth noting that recent discrete element model studies have found that: i) the fabric tensor evolves towards a critical state value with plastic deformation (Li and Li 2009) and ii) large volume contractions occur on imposition of stress rotation at the critical state (Theocharis et al 2017;Theocharis et al 2019). Capturing the above effects compatibly under evolving fabric anisotropy can be achieved through the recently developed framework of ACST (Anisotropic Critical State Theory) (Li and Dafalias 2012), wherein an anisotropy dependent additive term was used to modify ψ to control contractant versus or dilatant behaviour rather than the multiplicative factor adopted here (i.e.…”
Section: Key Features Of the Constitutive Modelmentioning
confidence: 87%